Implikasi Supervisi Akademik Dalam Meningkatkan Kinerja Guru Di Smp Negeri 1 Ciemas - Rima Erviana; Siti Qomariyah; Rubi Babullah; Nazrul Zimatul Rizky; Siti Nurafifah (Lembag, 2024)
The purpose of this study is to improve teacher performance through the implementation of academic supervision. The research method used is School Action Research (PTS) with a quantitative descriptive approach. Data collection techniques with observation, interviews, and documentation. Research results shows that academic supervision shows an increase in scores in aspects of learning planning and implementation. Although it is still in the sufficient category, it is because it continues to eventually increase. This result can be achieved because of good cooperation between the Principal and supervised teachers. The Principal discusses with the teacher the problems faced by the teacher in the process of planning and implementing lessons. Academic supervision carried out by the Principal is an effort to improve teaching, including stimulating, selecting the growth of positions and the development of teachers and revising learning objectives, teaching materials, methods, evaluation or assessment of teaching. Academic supervision can help teachers to learn and understand their duties and roles as educators.